Nanostructural and nanomechanical alterations of photosensitized lipid membranes due to light induced formation of reactive oxygen species - Ádám Zolcsák; Bálint Kiss; Tamás Bozó; Judit Somkuti; István Vona; Miklós Kellermayer; Levente Herenyi (Scientific Reports)
Abstract Photosensitization has a wide range of applications in vastly distant fields. Three key components must be present at the same time to trigger the related photodynamic effect: light, the photosensitizer (PS) and oxygen. Irradiating the sensitizer leads to the formation of reactive oxygen species (ROS). Since PSs are accumulated preferably in lipid membranes, the study of photoinduced damage to membrane lipids can greatly increase our understanding of the effect of ROS on membranes in pathological as well as therapeutic conditions. We aimed to characterize the topographical and nanomechanical changes in supported lipid bilayers (SLBs) evoked by light-induced ROS formation. SLBs were prepared on mica surfaces by deposition of liposomes containing unsaturated lipid components. Topographical changes of SLBs were imaged by atomic force microscopy (AFM), and ROS-induced nanomechanical alterations of the membranes were assessed by AFM force measurements. To shed light on chemical alterations of the membrane constituents, infrared spectra were recorded. In the AFM images of porphyrin-containing membranes nanoscopic, bilayer-spanning holes were detected after irradiation. The measured rupture forces increased as a result of irradiation. These phenomena did not occur in membranes lacking unsaturated lipid components, emphasizing their role in ROS-mediated disruption confirmed by infrared spectroscopy results.